2020
DOI: 10.1038/s41598-020-61276-9
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous optical coherence tomography for longitudinal volumetric assessment of intradermal volumes in a mouse model

Abstract: Clinical evaluation of skin lesions requires precise and reproducible technologies for their qualitative and quantitative assessment. In this study, we investigate the applicability of a custom-built dermatologic OCT system for longitudinal assessment of intradermal volumes in a mouse model. The OCT, based on an akinetic swept laser working at 1310 nm was employed for visualization and quantification of intradermal deposits of three different hyaluronic acid-based hydrogel formulations-one commercial and two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Optical coherence tomography (OCT) has recently emerged and been widely used in medical and biological research as a powerful imaging technique [ 7 , 8 , 9 , 10 ]. So far, a few interesting studies have demonstrated its feasibility in the RI measurement of some biological and medical materials [ 11 , 12 , 13 , 14 , 15 , 16 ]. The two current methodologies are focus-tracking and optical path matching.…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) has recently emerged and been widely used in medical and biological research as a powerful imaging technique [ 7 , 8 , 9 , 10 ]. So far, a few interesting studies have demonstrated its feasibility in the RI measurement of some biological and medical materials [ 11 , 12 , 13 , 14 , 15 , 16 ]. The two current methodologies are focus-tracking and optical path matching.…”
Section: Introductionmentioning
confidence: 99%